Spatial and Temporal Distribution of Blue Swimming Crab Larvae (Portunus pelagicus) in The Conservation Area of Betahwalang, Central Java - Sri Redjeki; Muhammad Zainuri; Ita Widowati; Abdul Ghofar; Elsa Lusia Agus; Mustagfirin Mustagfirin; Fabian Panji Ayodya; Michael Abbey (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2020)
Betahwalang has been one of the main contributors to the Blue Swimming Crab (BSC, Portunus pelagicus) fisheries production in Central Java Province. Recruitment of the BSC depends to a large extend on the abundance of crab larvae. However, information on larval distribution of the crab affecting the recruitment to the fishery, fishery management and decision making to support crab conservation in Betahwalang area has been lacking.  The purpose of this study is to describe the spatial and temporal distribution of BSC larvae in the crab conservation area, to identify the larval stage most commonly occurs in the conservation area, and to develop process of decision making to managing conservation areas. This study was conducted in twelve months, starting from January until December 2018. The spatial distribution of the crab larvae was analyzed and mapped by means of SPSS and ArcGIS. The results of this study indicate that the crab larvae occur in the conservation area throughout the year.  The highest larval abundance of the crab occurs in May, September, and November. The most commonly found crab larval stages were megalopa. As megalopa and crablet stages are relatively much more active and closer to the adult form, their occurrence in the conservation area and throughout the year of 2018 suggests the existence of continuous support to the Blue Swimming Crab recruitment for the following year. The spatial and temporal distribution of the larvae were influenced by oceanographic parameters including temperature, nitrate and phosphate, which were associated with monsoonal changes in the Java Sea.